Active mobility demand and active travel behaviour - Chua, Angeline Xin Ru (2018)
Active mobility, mainly in the form of walking and cycling, has been rising in importance as a form of transport in Singapore. As Singapore advocates to become a car-lite nation, walking and cycling are being highly encouraged as active modes of transport due to their efficient use of space, personal and social benefits. In order to understand the travel behaviours in Singapore, the analysis of the choice of transport modes in Jurong Lakeside District (JLD) are presented. This is a dual-student project where the trip analysis and travel behaviour are studied based on the trip purposes (covered in this report) and survey participants, age groups (Teow, 2018). The data obtained from Household Interview Travel Survey (HITS) 2012 is utilised in this study. To analyse trips, descriptive and inferential statistical approaches are utilised. Sample characteristics findings are used to reach conclusions regarding travel behaviour. As mentioned, trips are analysed by trip purposes. Trips to work and trips to school are the main points of consideration in this study. In addition, special interest is placed in trips and trip-stages that are performed by active modes of transport and short trip stages that are potential shifts to walking and cycling. Findings from the two different study scopes are compared and contrasted. Alternatives to further increase in active mobility transport rates are discussed accordingly. Analysis based on trip purposes concluded the trends for trip durations based on different modes of transport, peak hour for the different trip purposes and the various travel behaviours. Travel behaviours concerning short trips and first-last-mile (FLM) trip stages during the morning peak period are the main focus in this study. These trip stages are the base to start the encouragement drive for active mobility. Recommendations are then made to encourage more use of active mobility as a mode of transport for short trips or trip stages. Findings from the study reveal that the common peak period for the two trip purposes lies between 7:00 to 8:00 in the morning where heavy traffic condition is typical. It is also observed that public bus is the most commonly-used mode of transport for trips to work/school and trip stages for work and school trip purposes. Public buses operate under rigid schedules where the times of arrivals are separated into intervals. Travellers tend to spend less than 20 minutes on the public bus. However, this is during the duration for heavy traffic condition. Moreover, travellers are required to travel to the bus stops to board a bus. Therefore, it is feasible for these travellers to switch from public bus to active mobility given the convenience and flexibilty that they are going to be able to enjoy.